Condition dependence of female-specific UV-induced fluorescence in a jumping spider. (May 2017) - Painting, Christina J.; Chang, Chia-chen; Seah, Jia Fen; Li, Daiqin
Abstract : Male ornaments, commonly explained as being a result of sexual selection, are typically more elaborate than female ornaments. Interestingly, the bright and showy sexually selected traits of some female ornaments, like those of males, might be variable and condition dependent, and hence relate to individual quality. Ultraviolet (UV)-induced fluorescence is one such ornament known to be intricately involved in intraspecific communication in several animals; however, the role of fluorescence in signalling individual quality is unknown. The ornate jumping spider, Cosmophasis umbratica, exhibits female-specific UV-induced fluorescence on its palps to facilitate effective intersex communication but whether the fluorescence informs males of the female's condition and individual quality is unknown. We tested the prediction that UV-induced fluorescence in adult female C. umbratica depended on postmaturation age, mating status and feeding regime. We found that postmaturation age and feeding regime, but not mating status, affected female fluorescence. Middle-aged females were brighter than younger and older females, but the older females had a greener hue; well-fed females were brighter than starved females. We conclude that the UV-induced fluorescence of female C. umbratica is highly condition dependent, highlighting the importance of considering female as well as male ornamentation, particularly when this may have implications for mate choice and the maintenance of coloration in animals. Highlights: Female Cosmophasis umbratica jumping spiders have UV-induced fluorescing pedipalps. We investigated condition dependence of palp fluorescence in three experiments. Female age and feeding regime but not mating status affected palp fluorescence. Middle-aged females were brighter than younger or older females. Well-fed females were brighter than starved females.